Pectoralis Major Muscle Tear – Effectiveness Orthobiologic Nonoperative Treatment with Platet-Rich Plasma (PRP) Injections - Bieńko, Mateusz; Rutkowska, Marta; Marchaj, Magdalena; Putra, Anna; Nowakowski, Piotr; Król, Tomasz; Toborek, Michalina; Korta, Karolina; Niedziela, Natalia; Bednarz, Karolina (Quality in Sport, 2024)
Introduction Pectoralis major muscle ruptures, once considered rare, are now more common, especially in young male athletes and weightlifters involved in high-intensity sports. This injury can significantly impair upper limb function, leading to pain, weakness, and potential disability. Exploring and understanding available treatment options, particularly the promising role of orthobiologic therapies like PRP, is essential for optimizing recovery and achieving the best outcomes. Purpose The purpose of this review is to evaluate the effectiveness and the role of orthobiologic treatments such as PRP in enhancing healing and functional recovery for pectoralis major muscle ruptures. Conslusions The treatment of pectoralis major muscle ruptures requires a tailored approach that considers the injury's severity, the patient's activity level, and their goals. Nonoperative treatment can be effective for partial tendinous tears, muscle belly tears, muscle origin tears, and complete tendinous tears in sedentary individuals or when surgery is not feasible. Surgical intervention generally provides superior functional outcomes, particularly for athletes and those with complete ruptures. Orthobiologic treatments, such as ultrasound-guided PRP injections, provide a promising complement to conservative management, with potential benefits in pain reduction and accelerated functional recovery. Studies indicate that PRP-treated patients report higher satisfaction and better outcomes compared to those without PRP treatment. Nevertheless, many questions remain regarding the optimal formulation, dosage, and rehabilitation protocols for PRP. To fully understand PRP's effectiveness and refine its applications in sports medicine, more rigorous and long-term studies are needed. Additionally, further research is required to improve nonoperative treatment and rehabilitation protocols, ensuring optimal outcomes for all patients.